Pemetaan Sikap Penyesuaian Diri Mahasiswa di Perguruan Tinggi Pasca Kegiatan Pengenalan Budaya Akademik dan Kemahasiswaan (PBAK) - Sya’ban Maghfur (Journal on Education, 2023)
The purpose of this study was to describe the mapping of adjustment attitudes of BKPI students in tertiary institutions after the Introduction to Academic and Student Culture (PBAK) activities in terms of various dimensions of adjustment, gender and regional origin. This study uses a descriptive quantitative research method with a survey research design. The subjects of this study were BKPI students batch 2019 at IAIN Salatiga, totaling 89 students. Extracting data using questionnaires, observations, interviews and documentation then the results of the questionnaires were analyzed using descriptive percentage tables. The results of this study indicate that: 1) The implementation of PBAK 2019 can be accepted by students which correlates with the adjustment attitude of BKPI IAIN Salatiga students with a good percentage rate of 85.39% or 76 respondents and only 1.12% or 1 respondent who shows a very low level of adjustment. 2) The attitude of adjustment of BKPI IAIN Salatiga students after the 2019 PBAK activities can be mapped in various dimensions, the attitude of academic adjustment is at the good category level with a percentage of 73.03%. In the attitude of social adjustment (social adjustment) is at the good category level with a percentage of 71.91%. In the attitude of personal-emotional adjustment (personal-emotional adjustment) is at the good category level with a percentage of 62.92%. Meanwhile, the attitude of institutional adjustment is at a good category level with a percentage of 69.66%. 3) There is a similarity in the adjustment attitude of Islamic Education Guidance and Counseling students at IAIN Salatiga Post PBAK 2019 in terms of male and female gender. 4) Self-adjustment of Islamic Education Guidance and Counseling students at IAIN Salatiga Post PBAK 2019 seen in terms of regional origin (local and immigrants) explains that local students are better in terms of adjustment compared to immigrant students in various dimensions of academic, social, personal adjustment emotional and institutional.